Pattern of skin diseases in geriatric population: Our year-long experience from Nepal - Shraddha Uprety; Sangeeta Paudel; Pratichya Thapa (Wolters Kluwer Medknow Publications, 2021)
Introduction: The average life span has increased by about two decades in Nepal in last 30 years. With increasing longevity, geriatric health care is gaining much more importance. The statistical data regarding the geriatric skin disorders in Nepalese population is limited. The aim of this study to look for the patterns of skin diseases in the geriatric population of Nepal. Methodology: This is a retrospective, descriptive study where we reviewed the database of patients visiting the dermatology outpatient department of multispeciality teaching hospital in Nepal from August 2016 to July 2017. All patients from the age of 60 and above were included in the study. Data was analyzed using SPSS version 20. Chi square test was done where relevant. Result: Total of 918 patients were included in the study with mean age of 69 years. Most common presentation was that of dermatitis (32.2%) which was followed by infectious condition (29.4%), pruritus (7.4%), psoriasis (4.6%), urticaria (3.9%), miliaria (3.9%) and others. Among the dermatitis, 23% of the patients had hand or feet eczema and 23% had sebohrreic dermatitis. Variability according to weather was noticed with in presentation of sebohrreic dermatitis, dermatophytic infections, miliaria and herpes zoster. Conclusion: This study concludes that dermatitis, infections and pruritus are the most significant dermatological morbidities in our population. It highlights the need of zoster vaccine for our elderly population as it is not a part of the routine vaccination scheme in Nepal.